2009
DOI: 10.2215/cjn.02730608
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Therapy and Left Ventricular Mass Index in CKD and ESRD Patients

Abstract: Background and objectives: The purpose was to evaluate changes in the left ventricular mass index (LVMi) among anemic chronic kidney disease (CKD) and end-stage renal disease (ESRD) patients treated with recombinant human erythropoietin (EPO).Design, setting, participants, & measurements: A systematic review of the literature, reporting LVMi for patients before and after EPO therapy, was performed. The change in LVMi from baseline to the end of treatment was calculated and stratified by severity of anemia at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 34 publications
2
72
0
6
Order By: Relevance
“…Left-ventricular mass is a strong predictor of cardiovascular risk in dialysis patients, but unlike in the hypertensive population, regression does not necessarily portend improved outcomes; harm associated with complete correction of anemia is a case in point. [13][14][15][16][17] Even if left-ventricular mass regression were to reduce the risk of major adverse cardiovascular events, the magnitude of mortality risk reduction would likely be ,39%. 18 In addition, nonrandomized studies of frequent hemodialysis may elicit skepticism, because selection of appropriate controls is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Left-ventricular mass is a strong predictor of cardiovascular risk in dialysis patients, but unlike in the hypertensive population, regression does not necessarily portend improved outcomes; harm associated with complete correction of anemia is a case in point. [13][14][15][16][17] Even if left-ventricular mass regression were to reduce the risk of major adverse cardiovascular events, the magnitude of mortality risk reduction would likely be ,39%. 18 In addition, nonrandomized studies of frequent hemodialysis may elicit skepticism, because selection of appropriate controls is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Parfrey et al (82) recently reported on a meta-analysis of 15 unique, nonoverlapping trials (5 of which were randomized and controlled) involving 1731 subjects. LV mass was reduced by anemia correction by EPO administration only in those subjects who had severe anemia at baseline (Ͻ10 g hemoglobin/dl) and who were treated to a lower target hemoglobin level (Յ12 g hemoglobin/dl).…”
Section: What Are the Key Principles Of Management Of Lvh In Ckd And mentioning
confidence: 99%
“…Perhaps augmented gastrointestinal elimination of salt through orally administered exchange resins may help control inter-and intradialytic ECFV. Treatment of anemia has little effect on LV hypertrophy except when hemoglobin values are Ͻ10 g/dl (36).…”
Section: Disease Salt and Volumementioning
confidence: 99%